Implementasi Pendidikan Agama Islam Di Masa Covid-19 : Studi Kasus Pelaksanaan Pembelajaran Pai Di SMK Islamic Qon Gresik - Darmawan, Diaz Adi; Basri, Hasan; Yusuf Sya'bani, Mohammad Ahyan (STIT Muhammadiyah Paciran, 2022)
Qon Gresik Islamic Vocational School is a school that was established under the auspices of the AlQanaah Islamic Boarding School foundation. Qon Gresik Islamic Vocational School is a school located on Jalan Rantau Gang Masjid No.1 GKB, Manyar District, Gresik Regency, East Java Province. The large number of COVID-19 cases has hampered the learning process in schools, so the government through the ministry of education and culture issued a policy through circular letter number 4 of 2020. As stated in the second point, it was stated that the implementation of online learning was carried out to provide a learning experience. meaningful for students, without being burdened with the demands of completing all curriculum achievements for grade promotion and graduation. The change of the learning system into an online learning system as a result of the COVID-19 pandemic in its implementation has many obstacles, some students have difficulty, especially students whose homes are far from the reach of internet signals, coupled with the lack of mastery of technology from students' parents. thus resulting in learning delays. The purpose of this study was to find out how the implementation of Islamic religious education during the covid-19 period, and the obstacles and solutions in the implementation process. The author conducted research at Islamic Vocational School Qon Gresik by visiting the school and conducting interviews and observations. The sources in the interviews conducted by the author were the principal of the Qon Islamic Vocational School, the deputy head of the Qon Islamic Vocational School curriculum, the Islamic Religious Education subject teacher at Islamic Qon Gresik Vocational School.